Al-Bid‘ah versus al-Mashlahah al-Mursalah and al-Istihsân: Al-Syâthibî’s Legal Framework - Asep Saepudin Jahar (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstrak: al-Bid‘ah versus al-Mashlahah al-Mursalah dan al-Istihsân: Kerangka Hukum al-Syâthibî. Tulisan ini mengkaji pandangan Abû Ishâq al-Shâthibî (w. 790/1388) tentang bidah versus al-mashlahah al-mursalah  dan al-istihsân. Karya al-Syâthibî tentang konsep bidah dalam kitabnya, al-I'tishâm, sebagai respons terhadap ulama di zamannya yang menganggap bahwa al-mashlahah al-mursalah dan al-istihsân sebagai bentuk inovasi (al-bid‘ah). Tulisan ini akan mengelaborasi signifikansi gagasan al-Syâthibî dalam isu bidah yang memformulasikan kerangka syariah berbasis teks dan rasio dengan non-syariah. Pembahasan tentang bidah sebagai perbuatan yang bertentangan dengan prinsip syariah akan dianalisis dengan prinsip legalitas al-mashlahah al-mursalah  dan al-istihsân sebagai bagian dari metodologi penggalian hukum setelah Alquran, Sunah, ijmak, dan qiyâs. Tulisan ini juga ingin menguraikan keunggulan al-Syâthibî dalam epistemologi hukum dibanding ulama lain yang membahas isu serupa.Kata Kunci: al-istihsân, bidah, al-mashlahah al-mursalah, faqîh, teori hukumAbstract: Al-Bid‘ah versus al-Mashlahah al-Mursalah and al-Istihsân: Al-Syâthibî’s Legal Framework. This paper discusses with the juridical basis of Abû Ishâq al-Shâthibi’s (d. 790/1388) argument against those who considered al-mashlahah al-mursalah  (public interest) and al-istihsân (juristic preference) to be forms of innovation. The present discussion will examine the efficacy of al-Syâthibî’s distinction between al-bid‘ah (innovation), which is foreign and even contradictory to the shariah and the validity of the legal principles of al-mashlahah al-mursalah  and al-istihsân as subsidiary, yet valid sources of law under the Quran, the Sunnah, ijmâ’, and qiyâs (ratio legis). In addition, it will be shown how al-Syâthibî’s epistemological reliance on legal theory distinguished him from jurists who shared quite different views on the same matter. In the concluding remarks, the relevance of this theory with contemporary Muslim society with respect to pursuing legal practices is underlined.Keywords: al-istihsân, al-bid‘ah, al-mashlahah al-mursalah, faqîh, legal theoriesDOI: 10.15408/ajis.v12i1.975